Regulatory frameworks and theoretical assumptions of environmental education: a literature review study (Research, Society and Development, 2020)
Issues related to environmental degradation have been emphasized, worldwide, in the face of the environmental crisis that affects contemporary societies. This study, which is characterized as a bibliographic review, with a qualitative approach, aims to describe the regulatory frameworks of Brazilian environmental education and its theoretical assumptions. Environmental education, in the Brazilian historical context, is present in public policies and in the guiding documents of national education, conceived from major international conferences, usually organized by the UN and UNESCO, from the 1970s. The extent of environmental problems is also considered, from which needs emerge for a new social posture in relation to the environment. In this perspective, it is believed that the regulatory frameworks of Brazilian environmental education are not disconnected from basic education documents, in view of the prerogatives for the insertion of environmental education at all levels and modes of education.